Development of STEM-Based Module With Integrated Chemo-Entrepreneurship to Enhance Students’ Conservation Characters and Entrepreneurship - Ruliyanti, Tria; Sudarmin, Sudarmin; Wijayati, Nanik (International Journal of Active Learning, 2020)
This research was done due to the limited learning resources that can be used by students independently. The purpose of this research was to develop a module based on Science, Technology, Engineering and Mathematics integrated with Chemo-entrepreneurship to develop students' conservation character and entrepreneurship. This study used a research and development design (R&D). The data were obtained and analyzed by using descriptive percentage. The results of the module feasibility test done by the experts obtained an average of 84.8% with very feasible category for use. The students and teachers responses from Askhabul Kahfi and Lemuria Vocational High Schools showed 94% and 91% results with very good category. Based on the analysis of the cognitive learning outcomes of Askhabul Kafi and Lemuria students, it showed that students achieve an average completeness that exceeds 75, achieve classical completeness of more than 75% and experience an increase from the pretest and posttest scores. In addition, based on the observation of conservation character has increased with N-Gain 0.64 in the medium category and 0.73 with the high category. While the distribution of student entrepreneurial interest questionnaires has increased with an N-Gain of 0.68 in the moderate category and 0.79 with the high category. So these results suggest that the developed modules are effective to enhance the students’ conservation character and entrepreneurial interest.